NEOLIBERALISME: ANTARA MITOS DAN HARAPAN - Soesilowati, Etty (JEJAK: Jurnal Ekonomi dan Kebijakan, 2009)
Whether the government interference is necessary or not, has already everlasting theme in term ofthe history of economy policy. Most of people believed in vary of irrational myths that market mechanismwould be able to guarantee productivity, privatization would increase efficiency, the government roleshould be restricted and most of all, everything should be liberated to the private sector. It is unavoidablethat such policy contained certain implications. Deregulation policy that has been done so far, was one ofthe main factors of the bigger global policy that is liberalization of economy. However, does that globalpolicy was really useful for the public? Does privatization bring into people prosperity? DidnÃ¢â¬â¢tglobalization is only a myth that increased poverty and even huge gap between the have and the havenot? This paper is trying to study what neo liberalism is, what the policies, what is the government role,the strategic sectors that is colonized by foreign companies and, how intellectual should make theirmanner.Keywords: Neo liberalism, Myths, Expectation.